2022
DOI: 10.1007/978-3-030-93306-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genome Reduction in Microsporidia

Abstract: Microsporidia represent an evolutionary outlier in the tree of life and occupy the extreme edge of the eukaryotic domain with some of their biological features. Many of these unicellular fungi-like organisms have reduced their genomic content to potentially the lowest limit. With some of the most compacted eukaryotic genomes, microsporidia are excellent model organisms to study reductive evolution and its functional consequences. While the growing number of sequenced microsporidian genomes have elucidated geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 184 publications
5
33
1
Order By: Relevance
“…Our analysis suggests that this evolutionary transformation is primarily caused by changes in the msL1/msL2 ribosomal binding site. This finding is consistent with previous studies showing that microsporidian rRNA appears to evolve faster than microsporidian ribosomal proteins (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). It is, therefore, possible that microsporidian ribosomal proteins are frequently required to adapt to rRNA variations to compensate for rRNA variations.…”
Section: In Non-globular Proteins Structure Can Evolve Faster Than Se...supporting
confidence: 92%
“…Our analysis suggests that this evolutionary transformation is primarily caused by changes in the msL1/msL2 ribosomal binding site. This finding is consistent with previous studies showing that microsporidian rRNA appears to evolve faster than microsporidian ribosomal proteins (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). It is, therefore, possible that microsporidian ribosomal proteins are frequently required to adapt to rRNA variations to compensate for rRNA variations.…”
Section: In Non-globular Proteins Structure Can Evolve Faster Than Se...supporting
confidence: 92%
“…The phylogenetic tree generated using high-confidence proteasomal subunits ( Fig. 6a ) is consistent with trees derived from simplified rRNA or whole-proteome analyses 3,51 . Saliently, a comparison of the relative length and conservation of proteasomal subunits between microsporidia and selected eukaryotes to S. cerevisiae reveals widespread evidence of reductive evolution ( Fig.…”
Section: Resultssupporting
confidence: 69%
“…Indeed, two evolutionarily adjacent Nematocida spp. share only ∼68% of their sequence 48 , and even in complexes as universally conserved as ribosomes, yeast and microsporidian homologs are only 38% identical in sequence on average 3 . This sequence diversity confounds not only phylogenetic classification, but also attempts to identify microsporidian homologs, which hampers our functional understanding of these ecologically important organisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery potential is enormous and can be easily illustrated by recent studies on ribosomal structures of parasitic ribosomal subunits that revealed how reductive evolution may shape ribosome biogenesis and function. Moreover, unleashing these ‘new worlds’ will also open a window towards better understanding of major evolutionary constraints of ribosome synthesis and function [ 9 , 14 , 15 , 60 , 73 , 76 ].…”
Section: New World Unleashedmentioning
confidence: 99%